Endometriosis of the Inguinal Canal Mimicking a Hydrocele of the Canal of Nuck. (8th September 2020) - Basnayake, Oshan; Jayarajah, Umesh; Seneviratne, Sanjeewa Anuruddha
Abstract : Isolated presentation of endometriosis of the inguinal canal is infrequent, and the clinical and imaging findings may be misleading in such patients. We describe an otherwise healthy female with isolated inguinal endometriosis presenting as a hydrocele of the canal of Nuck. Surgeons should consider such unusual presentations and obtain imaging and histological evaluations in doubtful instances. Complete excision was curative in our patient with no evidence of recurrence.